Case report: Comprehensive exploration of a novel PFKM mutation in glycogen storage disease Type VII - Chen, Ying; Wang, Xinyu; Ji, Na; Fang, Qi; Chang, Xin; Liu, Meirong (Frontiers in Genetics, 2024)
Glycogen Storage Disease Type VII (GSD VII) is a rare glycogen metabolism disorder resulting from mutations in the PFKM gene, inherited in an autosomal recessive manner. It is characterized by exercise intolerance, muscle cramps, myoglobinuria, compensatory hemolysis, and later onset de novo myasthenia and mild myopathy, contributing to its clinical heterogeneity and diagnostic challenges. Here, we report a rare case of a 17-year-old Chinese woman exhibiting substantial muscle weakness and compensated hemolysis. Muscle biopsies showed glycogen deposition, and blood tests showed hyperuricemia and significantly elevated creatine kinase. Whole genome sequencing (WGS) and whole exome sequencing (WES) identified two compound heterozygous mutations in the PFKM (NM_000289.6) gene: c.626G>A and c.1376G>A in exons 7 and 15, respectively. According to the clinical presentation, diagnostic examination, and WES results, the patient was finally diagnosed with GSDVII. The discovery of these two new PFKM mutations expands the genetic spectrum, and understanding the clinical manifestations of these mutations is critical to preventing diagnostic delays and timely intervention and treatment.